2021
DOI: 10.1002/anie.202101186
|View full text |Cite
|
Sign up to set email alerts
|

E. coli Nickel‐Iron Hydrogenase 1 Catalyses Non‐native Reduction of Flavins: Demonstration for Alkene Hydrogenation by Old Yellow Enzyme Ene‐reductases**

Abstract: A new activity for the [NiFe] uptake hydrogenase 1 of Escherichia coli (Hyd1) is presented. Direct reduction of biological flavin cofactors FMN and FAD is achieved using H 2 as a simple, completely atom-economical reductant. The robust nature of Hyd1 is exploited for flavin reduction across a broad range of temperatures (25-70 8C) and extended reaction times. The utility of this system as a simple, easy to implement FMNH 2 or FADH 2 regenerating system is then demonstrated by supplying reduced flavin to Old Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In our previous batch studies, we focused on co-immobilizing a separate NAD + reductase (a protein possessing just the NAD + reductase activity of the SH) with a more robust hydrogenase (E. coli hydrogenase 1, "Hyd1") onto carbon particles; this system yielded much higher stability and cofactor regeneration activity compared with the SH. For reference, we have demonstrated that Hyd1 itself maintains activity after >5 days of continual H 2driven operation (FMN recycling in this case) at room temperature (Joseph Srinivasan et al, 2021). For this two-enzyme catalyst, the carbon plays dual roles, acting as an enzyme support and also electronically linking the enzymes by conducting electrons generated via H 2 -oxidation by the Hyd1 to the NAD + reductase, thereby powering the NAD + reductase to regenerate NADH.…”
Section: Results and Discussion H 2 -Driven Nadh Recyclingmentioning
confidence: 94%
See 2 more Smart Citations
“…In our previous batch studies, we focused on co-immobilizing a separate NAD + reductase (a protein possessing just the NAD + reductase activity of the SH) with a more robust hydrogenase (E. coli hydrogenase 1, "Hyd1") onto carbon particles; this system yielded much higher stability and cofactor regeneration activity compared with the SH. For reference, we have demonstrated that Hyd1 itself maintains activity after >5 days of continual H 2driven operation (FMN recycling in this case) at room temperature (Joseph Srinivasan et al, 2021). For this two-enzyme catalyst, the carbon plays dual roles, acting as an enzyme support and also electronically linking the enzymes by conducting electrons generated via H 2 -oxidation by the Hyd1 to the NAD + reductase, thereby powering the NAD + reductase to regenerate NADH.…”
Section: Results and Discussion H 2 -Driven Nadh Recyclingmentioning
confidence: 94%
“…Biocatalysts for H 2 -driven cofactor recycling (SH and Hyd1) were prepared in-house. Detailed protocols for expression and purification of the hydrogenases [Escherichia coli hydrogenase 1, Hyd1 (Joseph Srinivasan et al, 2021), and R. eutropha soluble hydrogenase, SH (Lauterbach and Lenz, 2013)] have been described previously. Alcohol dehydrogenase ADH-105 was provided by Johnson Matthey in the His-tagged and purified form.…”
Section: General Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, a report by the Vincent group suggested that Nickel‐Iron Hydrogenase 1 of Escherichia Coli can reduce the flavin cofactor using H 2 as the reductant, [66] with a turnover frequency of up to 20.4 min −1 . The Hydrogenase enzyme could recycle the reduced cofactor using clean atom efficient reductant H 2 that helped to continue the asymmetric reduction by ene‐reductases.…”
Section: Single Reduction and Individual Er‐catalysed Processesmentioning
confidence: 99%
“…[64] Recently, a novel affinity tag ((HR) 4 -tag) (a combination of polyHis-tag and polyArg-tag) was used to immobilize ene-reductase enzymes on non-functionalized magnetic nanoparticles. [65] Lately, a report by the Vincent group suggested that Nickel-Iron Hydrogenase 1 of Escherichia Coli can reduce the flavin cofactor using H 2 as the reductant, [66] with a turnover frequency of up to 20.4 min À 1 . The Hydrogenase enzyme could recycle the reduced cofactor using clean atom efficient reductant H 2 that helped to continue the asymmetric reduction by ene-reductases.…”
Section: Immobilized Enzymatic Reductionsmentioning
confidence: 99%